2021
DOI: 10.1109/tdsc.2019.2897663
|View full text |Cite
|
Sign up to set email alerts
|

On Evaluating Fault Resilient Encoding Schemes in Software

Abstract: Cryptographic implementations are often vulnerable against physical attacks, fault injection analysis being among the most popular techniques. On par with development of attacks, the area of countermeasures is advancing rapidly, utilizing both hardware-and software-based approaches. When it comes to software encoding countermeasures for fault protection and their evaluation, there are very few proposals so far, mostly focusing on single operations rather than cipher as a whole. In this paper we propose an eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…For the protected implementation, there is a register precharge (see e.g. Section 5.1 of [38]) of both input registers and the output register (3 × 1 clk cycle), followed by the operand loading (2 × 1 clk cycle) and table look-up (2 clk cycles), resulting into 7 clock cycles. Regarding the area overhead, as stated in [38], in case the codeword size is ≤ 8 bits, there is a fixed table size of 65 kB per binary operation (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the protected implementation, there is a register precharge (see e.g. Section 5.1 of [38]) of both input registers and the output register (3 × 1 clk cycle), followed by the operand loading (2 × 1 clk cycle) and table look-up (2 clk cycles), resulting into 7 clock cycles. Regarding the area overhead, as stated in [38], in case the codeword size is ≤ 8 bits, there is a fixed table size of 65 kB per binary operation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation level techniques aim at detecting changes in the intermediate data. Detection can be achieved by using various encoding techniques, ranging from simple ones such as parity [37], to sophisticated codes that can be customized to protect against specific fault models [38]. Another approach is performing the computation several times and comparing the result.…”
Section: Overviewmentioning
confidence: 99%
“…Therefore, researchers try to design a countermeasure which is capable of protecting against both [SMG16; BH17]. Ways to find efficient codes and to evaluate the encoding-protected cipher implementations are studied in [BHL19].…”
Section: Detectionmentioning
confidence: 99%
“…It is worth noting that we can obtain appropriate estimates of N , m , r by using BDS statistics. Brock et al 46 made several important asymptotic distributions, and the mathematical statistics results showed that when2m5,N500,σ2r2σ, the asymptotic distribution can be well approximated by a finite sequence and that0.33emnormalS(m,N,r,1) can represent correlation of sequences. Moreover, the selection of time delay is independent of the value of embedded dimension m .…”
Section: Smis Reliability Prediction Based On Failure Time Sequencementioning
confidence: 99%
“…Compared with multimodel synthesis methods, fault data fusion methods have improved the prediction accuracy. Fault data fusion methods 42–46 can be divided into two categories: (1) Taking hardware correlation failure as the main manifestation of systems failure, a system impact model is established for software correlation failure, which is then converted into systems failure and comprehensively evaluated. (2) Taking software correlation failure as the main manifestation of system failure, a system impact model is established for hardware correlation failure, which is then converted into system failure and comprehensively evaluated.…”
Section: Introductionmentioning
confidence: 99%